Health-related quality of life and its predictors among chronic kidney disease patients: A hospital-based cross-sectional study. - Tasmia Tasnim; Kazi Muhammad Rezaul Karim; Tanjina Rahman; Harun-Ur Rashid (PLoS ONE)
Chronic kidney disease (CKD) has a significant impact on the health-related quality of life (HRQoL) of affected individuals due to its progressive and disabling nature. The aim of this study was to evaluate the HRQoL and its predictors among CKD patients. A cross-sectional study was carried out at kidney foundation Hospital and research Institute at Dhaka, Bangladesh. Kidney Disease Quality of Life (KDQoL™ -36) questionnaire were used to measure the HRQoL of CKD patients. The study also used kidney-targeted KDQoL-36 Summary Score (KSS). Socio-demographic and medical records were also collected. Descriptive statistics, and multiple linear regression were performed. Out of 430 patients, 77.9% were in moderate to advanced stage of CKD. Patients aged, occupation, income, co-morbidities such as diabetes or hypertension, medication used, and serum hemoglobin were found significantly (p <0.05) associated at different stages of CKD. The mean domain scores of physical component summary (PCS), mental component summary (MCS), burden of kidney disease (BKD), effect of kidney disease (EKD), symptoms and problems of kidney disease (SPKD) subscales were 37.19, 45.94, 31.49, 63.95, and 73.35, respectively. The KSS was 63.24. The stage of CKD has been documented as an important predictor of HRQoL of all subscales of KDQoL-36 as well as KSS. The older age group also showed a clear link with a lower HRQoL in all subscales of KDQoL-36, except SPKD. In multiple linear regression analysis, stage of CKD, patients age, employment status and use of medication were found significant predictors of KSS. Further, higher levels of education, being married, absence of diabetes and heart disease were all independent predictors of a higher MCS. Whereas retirement, low duration of CKD and the use of three or more drugs strongly linked to worse scores of PCS. By addressing the determinants of poor HRQoL, healthcare providers can tailor treatment plans to better meet the needs of these individuals and ultimately enhance their overall well-being.